Prevalence and Determinants of the Double Burden of Malnutrition at Household Level: A Systematic Review - Sufyan, Dian Luthfiana; Soe, Le Thandar; Hasan Syah, Muhammad Nur; Wahyuningsih, Utami; Marjan, Avliya Quratul; Noor, Sutamara Lasurdi (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2024)
The persistent problem of undernutrition and the emerging prevalence of overnutrition hints at a new term for the double burden of malnutrition among children globally. This study aims to provide a review of the published studies concerning the prevalence of double burden of malnutrition at the household level and the associated factors. Articles were identified from the electronic databases of PubMed, Nature, SAGE, Scopus, and SpringerLink, using the same search terms for all. A total of fourteen articles were eligible and sixteen sets of prevalence values were obtained. Most articles were published in 2018 – 2020. Fourteen articles used secondary data from the Demographic and Health Survey. Most articles studied under five children and mothers 15-49 years. Mother’s nutritional status was identified using BMI, while for children height for age z-score was commonly used. The reported prevalence of double burden at the household level varied from 1.0 to 28.0% by country. Frequently assessed factors observed that older children and older mothers were likely to develop a household double burden of malnutrition. A negative association was found when households possessed access to mass media. Overall, the media should have been channels for health promotion. Intervention concerning the nutrition of mothers and children at the household level is required to be intensified through nutrition-specific and nutrition-sensitive programs.